1954
DOI: 10.1103/physrev.94.1218
|View full text |Cite
|
Sign up to set email alerts
|

Neutron Capture in the Separated Isotopes of Platinum

Abstract: Using the separated isotopes of platinum, irradiated in the pile, the energies of the gamma rays for the activities of Pt 191 , Pt 193 , and Pt 195 have been evaluated. For Pt 191 fifteen gamma rays are found which fit well a simple level scheme. Pt 193 emits isomerically a gamma ray followed by K capture to iridium, with the possible emission of a high-energy gamma. Pt 196 emits a highly converted gamma ray followed by two others in rapid succession decaying to the stable isotope. The half-lives of the three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1955
1955
1988
1988

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…The 0.081-Mev transition has been observed in the decay of Ptl" by Cork et al (1954) and Gillon et al (1954) but it has not previously been shown to accompany the OslgL decay. The L1: L2: L3 ratio found here is in excelleilt agreement with the 0.6: 1.1: 1.0 ratio found by Gillon and clearly identifies the transition as a M l + E 2 mixture.…”
Section: Experimental Results-os'~~mentioning
confidence: 90%
“…The 0.081-Mev transition has been observed in the decay of Ptl" by Cork et al (1954) and Gillon et al (1954) but it has not previously been shown to accompany the OslgL decay. The L1: L2: L3 ratio found here is in excelleilt agreement with the 0.6: 1.1: 1.0 ratio found by Gillon and clearly identifies the transition as a M l + E 2 mixture.…”
Section: Experimental Results-os'~~mentioning
confidence: 90%
“…A 129.1-kev gamma ray going to the ground state of Ir 191 has been observed both from the decay of Os 19115_19 and of Pt 191 . 10 ' 20 The gamma ray has a K = 2A and K/L = 2.2 and thus the transition is a mixture of Ml and £2. Identifying this with the observed gamma ray, the discrepancy in K/L ratios would be explained by a highly ^-converted gamma ray corresponding to the rate determining transition.…”
Section: Platinummentioning
confidence: 99%